The Existence Of Customary Leaders in Land Dispute Resolution - Ridwan Bustam; Ilham Abbas; Muhammad Zulkifli Muhdar (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to determine and analyze the existence of the Tu'a Golo traditional figure in resolving land disputes in the indigenous people of Boleng District, Manggarai Bara Regency, East Nusa Tenggara. To determine and understand the factors that influence the resolution of land disputes in the Tu'a Golo traditional figure in the indigenous people of Boleng District. This study uses an empirical legal research type. The location of the research is in the Customary Law area of ​​Boleng District, West Manggarai Regency, East Nusa Tenggara Province. The types and sources of data are Primary and Secondary Data obtained through interview and documentation techniques, then qualitative analysis is carried out. The results of the study show that the existence of the traditional figure Tu'a Golo in the process of resolving land disputes in the traditional community of Boleng District, West Manggarai Regency, East Nusa Tenggara was resolved by Tu'a Golo as a traditional figure. The factors that influence the process of resolving land disputes in the traditional figure Tu'a Golo in the traditional community of Boleng District are internal factors from Tu'a Golo himself and external factors from the community. The recommendation of this study is that Tua Golo conduct socialization of the applicable customary law so that the community prioritizes resolving social and cultural problems through deliberation and consensus. As the customary leader or Hatoe Kampoh, Tu'a Golo always pays attention to his traditional community by being a fair mediator so that he is not influenced by any party. Abstract: This study aims to determine and analyze the existence of the Tu'a Golo traditional figure in resolving land disputes in the indigenous people of Boleng District, Manggarai Bara Regency, East Nusa Tenggara. To determine and understand the factors that influence the resolution of land disputes in the Tu'a Golo traditional figure in the indigenous people of Boleng District. This study uses an empirical legal research type. The location of the research is in the Customary Law area of ​​Boleng District, West Manggarai Regency, East Nusa Tenggara Province. The types and sources of data are Primary and Secondary Data obtained through interview and documentation techniques, then qualitative analysis is carried out. The results of the study show that the existence of the traditional figure Tu'a Golo in the process of resolving land disputes in the traditional community of Boleng District, West Manggarai Regency, East Nusa Tenggara was resolved by Tu'a Golo as a traditional figure. The factors that influence the process of resolving land disputes in the traditional figure Tu'a Golo in the traditional community of Boleng District are internal factors from Tu'a Golo himself and external factors from the community. The recommendation of this study is that Tua Golo conduct socialization of the applicable customary law so that the community prioritizes resolving social and cultural problems through deliberation and consensus. As the customary leader or Hatoe Kampoh, Tu'a Golo always pays attention to his traditional community by being a fair mediator so that he is not influenced by any party.